Impact of Relevant Computer Softwares on Osun State Secondary School Students and Its Learning Effectiveness in Mathematics - Abanikannda, Mutahir Oluwafemi; Enoch, Oloyede Oluwayemi (Jurnal Penelitian Pendidikan, 2024)
The study investigated the relevance of computer software on Osun State high school students learning effectiveness in mathematics. The study is descriptive; a sample of 300 students from Osogbo Local Government, Osun State formed the participants for the study. The instrument for data collection was a questionnaire and checklist and the reliability level was 0.75. Data collected were analyzed using descriptive statistics specifically, using percentage, mean, t-test, and Pearson Moment Correlation Co-efficient. The findings of the study revealed that the use of computer instruction improves students’ achievement in mathematics at high schools’ level. Application software available for teaching and learning of mathematics as 3D grapher, advanced grapher software, curve fitting, algae programming, autograph, 3d shaped figure, rotation and reflection, vectors, graphs, graphic calculator, data fit software, math type, probability and statistics, brain builder math edition and efofex. Hence, there is a significant difference in the achievement of students target with application software tools in mathematics and those not target with application software tools. The following recommendations were made such as: a digital classroom that will contain adequate computer instructions should be put in place for mathematics teachers, students should be encouraged by teachers on the benefits of computer instruction for learning, and strategies should be designed on how students can be discouraged from undue commitment to computer software use for purposes other than education, employers of teachers should give sufficient technical skills to their employees on computer instruction so as to make them competent with the use of computer software.